A CFD study on improving air flow uniformity in indoor plant factory system. (July 2016) - Zhang, Ying; Kacira, Murat; An, Lingling
Abstract : Indoor plant factories are one of the alternative ways to meet the demands of food production for the increased urban dwellers. It enables growers to grow food crops consistently and locally with high quality. In an indoor plant factory, a forced convection based ventilation and circulation system is used to control the growing environment and maintain climate uniformity. Lettuce is a common leafy crop grown in indoor plant factories and an improper design could cause the tip burn of lettuces which usually occurs at inner and newly developing leaves with low transpiration rate due to the existence of a stagnant boundary layer under high transpiration demand. A three-dimensional computational fluid dynamics (CFD) model was developed and validated through simulating the growing environment in a single shelf production system. An improved air circulation system was designed and proposed to help providing a dynamic and uniform boundary layer which could help preventing tip burn occurrences in lettuce production. A perforated air tube with three rows of air jets was designed to provide vertical air flow down to the crop canopy surface. Four cases with the perforated air tubes were compared with a control treatment. The results indicated that the case with two perforated air tubes was able to provide an average air velocity of 0.42 m s −1 with a coefficient of variation of 44%, which was recommended as the optimal design of air circulation system among four cases in this study. Highlights: 3D-CFD model simulating growing environment in a single shelf production system. Improved air circulation system proposed to help prevent tip burn in lettuce. Perforated air tube with three rows of air jets to provide vertical air flow to crop. Four cases with the perforated air tubes were compared with a control treatment. Two perforated air tubes able to provide recommended air circulation system.